Studies on polymer-metal interfaces, 3 - An analysis of interfacial characteristics between amine-functionalized polystyrene/copper and between hydroxyl-functionalized polystyrene/copper - Kim, DH; Kim, KH; Jo, WH; Kim, J (WILEY-V C H VERLAG GMBH, 2000)
Full Paper: The interfacial characteristics between amine-functionalized polystyrene/copper and between hydroxyl-functionalized polystyrene/copper were investigated by adhesion strength measurements and reflection absorption infrared (RAIR) spectroscopy. Poly(styreneco-4-co-4-aminostyrene) (PS-NH2) and poly(styrene-co-4-hydroxystyrene) (PS-OH) containing ca. 1.5 and 1.7 mol-% of comonomers, respectively, were synthesized by anionic polymerization. The adhesion strength between PS-OH and copper is higher than that between PS-NH2 and copper. The analysis with RAIR spectroscopy shows that both the NH2 group in PS-NH2 and the OH group in PS-OH interact specifically with the copper surface. RAIR spectroscopy also shows that the OH group in PS-OH is oriented in a parallel direction to the copper surface and that the C-O bond is oriented in a direction slightly inclined from the normal surface. The MH2 group in PS-NH2 has two orientations, while the orientation of the C-N bond could not be identified precisely from the RAIR spectrum. [GRAPHICS] Schematic illustration of the transition dipole moment directions of the symmetric and asymmetric NH2 stretching modes onto metal surface for two different orientations.
Keywords: ENHANCED RAMAN-SCATTERING; SELF-ASSEMBLED FILMS; CHEMICAL INTERACTIONS; SURFACE; XPS; ADSORPTION; IMIDAZOLE; ADHESION; SERS; GOLD